2019
DOI: 10.1155/2019/6914849
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Derived Damage-Associated Molecular Patterns in Sepsis: From Bench to Bedside

Abstract: Sepsis is one of the most serious health hazards. Current research suggests that the pathogenesis of sepsis is mediated by both pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs). Mitochondria are among the most important organelles in cells and determine their life and death. A variety of mitochondria-derived DAMPs (mtDAMPs) are similar to bacteria because mitochondria are derived from bacteria according to the mitochondrial endosymbiotic theory. Their activated si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 99 publications
0
17
0
Order By: Relevance
“…Mitochondrial structural and functional derangements in proximal tubular epithelial cells have also been reported in experimental sepsis models [ 5 ]. The inflammatory response in sepsis-induced kidney injury might be associated with the release of pro-apoptotic factors and mitochondria-derived DAMPs [ 25 ]. Moreover, the induction of apoptosis and functional alterations in podocytes and tubular cells after treatment with plasma from patients with sepsis-induced AKI suggests that circulating plasma factors augment kidney injury [ 26 ].…”
Section: Mitochondrial Dysfunction In Acute Kidney Injurymentioning
confidence: 99%
“…Mitochondrial structural and functional derangements in proximal tubular epithelial cells have also been reported in experimental sepsis models [ 5 ]. The inflammatory response in sepsis-induced kidney injury might be associated with the release of pro-apoptotic factors and mitochondria-derived DAMPs [ 25 ]. Moreover, the induction of apoptosis and functional alterations in podocytes and tubular cells after treatment with plasma from patients with sepsis-induced AKI suggests that circulating plasma factors augment kidney injury [ 26 ].…”
Section: Mitochondrial Dysfunction In Acute Kidney Injurymentioning
confidence: 99%
“…In addition, the gasdermin pore in the plasma membrane eventually executes pyroptosis, simultaneously causing the mitochondria to release its contents [ 32 ]. The ROS, mtDNA, and ATP released from injured mitochondria strongly promote pyroptosis by activating the inflammasome and the cleavage of caspase-1 [ 33 35 ]. Our results have shown that HGF protects the integrity of the mitochondrial plasma membrane, reduces the release of mitochondrial contents, leads to the scavenging of ROS or other mitochondrial damage-associated molecules and prevents pyroptosis [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The elevated ROS and RNS induces DNA strand break-mediated PARP activation causing reduction in the cellular NAD + level, oxidative phosphorylation abnormalities, and mPT induction [168]. All these processes lead to the release of various small molecules, such as ATP and succinate, and macromolecules, or their fragments, such as mitochondrial DNA, RNA, transcription factor, cytochrome C, cardiolipin and N-formyl peptides, collectively referred to as mitochondria-derived damage-associated molecular patterns (mtDAMPs) [169]. The mtDAMPs are recognised by their associated pattern recognition receptors that induce various inflammatory processes, overactivation of which is responsible for the development of sepsis and septic shock [170].…”
Section: Sepsis and Septic Shockmentioning
confidence: 99%
“…The mtDAMPs are recognised by their associated pattern recognition receptors that induce various inflammatory processes, overactivation of which is responsible for the development of sepsis and septic shock [170]. Due to mitochondrion's prokaryotic origin, mtDAMPs are similar to molecular patterns of most pathogens, and are likely to trigger excessive inflammatory reactions, which can aggravate sepsis to multi-organ dysfunction syndrome and death [169]. Activation of the inflammatory processes by mtDAMP can further damage mitochondria, forming a vicious circle that is a potential target regarding therapy.…”
Section: Sepsis and Septic Shockmentioning
confidence: 99%